FENOMENA PRAKTIK IBADAH SHALAT BERJAMA’AH DAN DAMPAK SOSIALNYA DALAM PERSPEKTIF LINTAS MAZHAB (STUDI PADA MASJID AL-AMANAH KOTA PALU) - Rahmat; Hidayatullah, Muhammad Syarief; Imron, Ali (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This paper examines in depth the practice of congregational prayer at the Al-Amanah Mosque in Palu City, with a focus on the diversity of existing schools of thought. It uses a qualitative descriptive method. Data collection techniques are carried out using observation, interview, and documentation methods. Data analysis techniques used are data triangulation, data comparison, and checking the validity of data. The results of the study show significant differences in the practice of congregational prayer, especially between the Maliki and Syafi'i schools of thought, which are reflected in the procedures for reading the basmalah and carrying out dhikr. This difference, if not managed properly, has the potential to trigger horizontal conflict in the community. So, the difference in schools of thought in the practice of congregational prayer at the Al-Amanah Mosque in Palu City is a complex and multi-faceted phenomenon. To create a good atmosphere in the implementation of prayer, joint efforts are needed from all parties, both from the community, mosque administrators, religious leaders, and the congregation itself.